Transitivity Processes And Genre Conformity In SMA IT Unggul Al Munadi Medan Recount Texts - Naufal Nasution (Universitas Negeri Medan, 2026)
This study investigates transitivity processes in personal recount texts written by tenth-grade EFL students at SMA IT Unggul Al Munadi Medan and examines how those processes align with the linguistic features of the recount genre as defined within Systemic Functional Linguistics (SFL). There have been many studies about transitivity in the writing of Indonesian students learning English as a foreign language. But no study has looked at all three parts of the transitivity system (the types of processes, the roles of the participants, and the circumstances) together. It also has not looked at the findings through the language features based on the types of writing that Martin (1992) and Gerot and Wignell (1994) established. A qualitative descriptive design was adopted by this study, and Halliday and Matthiessen's (2014) Transitivity framework was applied to a corpus of 18 student-produced recount texts, giving rise to 329 annotated clauses. The data were analyzed using Miles, Huberman, and Saldaña's (2014) dynamic model. Findings show that Material processes dominate at 43.2%, followed by Relational (23.7%) and Mental (23.1%) processes, while secondary process types collectively account for 10%. Most texts fit into three categories based on how they use language. These categories are material process dominance, first-person participant configuration with a variety of roles, and temporal circumstantial groundedness. Though most texts generally fit into these categories, there are some exceptions. These exceptions include texts where mental processes replace material sequences, where participant diversity is limited to the self-referential